2008
DOI: 10.1016/j.bbamem.2007.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane localization of cis-isomers of zeaxanthin in the host dimyristoylphosphatidylcholine bilayer membrane

Abstract: The effects of the 9-cis and 13-cis isomers of zeaxanthin on the molecular organization and dynamics of dimyristoylphosphatidylcholine (DMPC) membranes were investigated using conventional and saturation recovery EPR observations of the 1-palmitoyl-2-(14-doxylstearoyl)phosphatidylcholine (14-PC) spin label. The results were compared with the effects caused by the all-trans isomer of zeaxanthin. Effects on membrane fluidity, order, hydrophobicity, and the oxygen transport parameter were monitored at the center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…However, distinct intramembrane localization of the stereoisomers may explain their different behavior. In agreement with this idea, Widomska and Subczynski have demonstrated that cis and trans isomers of zeaxanthin have different orientations in dimyristoyl phosphatidylcholine bilayer membranes and thus can modify the biophysical membrane properties, including the hydrophobicity and membrane fluidity at different depth of the membrane 40 . In accordance with this report our fluorescence anisotropy measurements revealed that the retinoid derivatives interacting with the transporters retinyl-acetate, 13- cis -retinoic acid and retinol selectively increase the membrane viscosity and packing density in the depth of the membrane monitored by DPH, while ATRA and 9- cis -retinoic acid did not have any effect ( Fig.…”
Section: Discussionmentioning
confidence: 71%
“…However, distinct intramembrane localization of the stereoisomers may explain their different behavior. In agreement with this idea, Widomska and Subczynski have demonstrated that cis and trans isomers of zeaxanthin have different orientations in dimyristoyl phosphatidylcholine bilayer membranes and thus can modify the biophysical membrane properties, including the hydrophobicity and membrane fluidity at different depth of the membrane 40 . In accordance with this report our fluorescence anisotropy measurements revealed that the retinoid derivatives interacting with the transporters retinyl-acetate, 13- cis -retinoic acid and retinol selectively increase the membrane viscosity and packing density in the depth of the membrane monitored by DPH, while ATRA and 9- cis -retinoic acid did not have any effect ( Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Monopolar β-cryptoxanthin is also less soluble in the lipid bilayer than macular xanthophylls [41]. Interestingly, the tendency of cis -isomers of xanthophylls to aggregate is usually much less than their all- trans counterparts [42,43], and they also affect membrane properties more strongly (the effect of zeaxanthin on membrane properties increases in the direction: all- trans < 9- cis ≤ 13- cis [44]). Cis -isomers are also more readily solubilized, absorbed, and transported [42].…”
Section: Transport Of Macular Xanthophylls and Their Solubility And Omentioning
confidence: 99%
“…Orientation of polar and nonpolar carotenoids (including their cis -forms) in the lipid-bilayer membrane has been investigated by many laboratories [19,44,47,58,59]. It is suggested that the presence of polar hydroxyl groups at the ends of carotenoid molecules and their transmembrane orientation (as in the case of zeaxanthin and lutein) enhance their antioxidant properties , as compared with the antioxidant properties of monopolar (β-cryptoxanthin) and nonpolar (β-carotene) carotenoids [40,60].…”
Section: Antioxidant Potency Of Macular Xanthophylls In Membranesmentioning
confidence: 99%
“…magnetic resonance (NMR) [21] spectroscopy, diffractometry [22,23], monolayers technique [24], and others. However, the effect of the cis-isomers of carotenoids on the membrane properties is less investigated [25,26].…”
Section: Accepted Manuscriptmentioning
confidence: 99%